Occurrence of gastric ulcers in horses exercised on a treadmill - Ribeiro,Gesiane (2016)
ABSTRACT: The most frequently causes of gastric ulcers in horses are fasting, feeding type and management, as well as administration of certain medications. More recently, exercise has also been identified as an important factor in the development of gastric lesions in athlete horses. The purpose of the present study was to assess whether treadmill exercise predisposes the horses to the occurrence of gastric ulcers. Five Arabian horses underwent a twelve-week training period on a treadmill and a gastroscopic evaluation before and after the training period. All animals showed gastric lesions after the training period. Based on these results, it is concluded that Arabian horses undergoing exercise on a treadmill may develop gastric lesions varying in number and severity.